The welfare gain from switching to tax regulation of fisheries - Frank Jensen; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2017)
Theoretical papers find that taxes are preferred over individual transferable quotas (ITQs) when fisheries regulators are uncertain about either biological growth or the extent of non-compliance with regulations. However, the size of the welfare gain from switching to taxes has not previously been investigated empirically. Based on estimated profit and growth functions, we simulate this gain for the Danish cod fishery in the Kattegat and find a welfare gain of less than 2%. We also develop a simple indicator which can be used to approximate the welfare gain of switching to tax regulation for other fisheries. The value of the indicator is calculated for a number of fisheries worldwide for which the necessary data have been published and we find that the gain from a switch to taxes is typically between 1.5% and 2.5% (in no case greater than 4.2%). We, therefore, conclude that the switch to tax regulation of fisheries, which has been recommended in prior theoretical literature, is of little practical importance.
Keywords: Q22; C54; D62; H23; Q28; 330; taxes; ITQs; uncertainty; cod in Kattegat; actual welfare gain